A high infrared reflectance Cu-TiO2 composite coating and its preparation method
By introducing TiO2 ceramic particles into a copper substrate using cold spraying technology, a Cu-TiO2 composite coating was prepared, which solved the problems of easy oxidation and insufficient mechanical strength of copper coatings. This achieved a synergistic improvement in high infrared reflectivity and high hardness, making it suitable for fields such as optical devices and solar collectors.
Patent Information
- Application Number
- CN202610854326.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-06-13
- Publication Date
- 2026-08-25
AI Technical Summary
Existing copper coatings are prone to oxidation in air and have limited mechanical strength, making it difficult to maintain high infrared reflectivity and durability in harsh environments. Traditional improvement methods are costly or have problems such as poor adhesion and thermal expansion mismatch.
TiO2 ceramic particles were introduced into a copper substrate using cold spraying technology. Cu and TiO2 powders were mixed by mechanical ball milling, and the cold spraying process parameters were optimized to prepare a Cu-TiO2 binary composite coating. The high infrared reflectivity, hardness, and chemical inertness of TiO2 were utilized to achieve synergistic optical enhancement and dispersion strengthening of the coating.
It achieves an increase in infrared reflectivity without decreasing it, improved coating hardness, enhanced wear resistance and oxidation resistance, reduced cost, and suitability for mass production. It is applicable to fields such as optical devices, solar collectors and infrared reflective screens.
Smart Images

Figure CN122629463A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of infrared reflective coating technology, and more specifically, to a Cu-TiO2 binary composite coating with high infrared reflectivity and its cold spray preparation method. Background Technology
[0002] Copper (Cu) possesses excellent intrinsic infrared reflectivity, making it a promising candidate for applications in optical devices, solar collectors, and infrared reflective screens. However, copper is highly susceptible to oxidation in air, and the resulting copper oxide (CuO) or cuprous oxide (Cu2O) significantly reduces its reflectivity. Furthermore, pure copper has limited mechanical strength and is easily scratched and corroded, severely impacting its service life in harsh environments.
[0003] Currently, common methods for improving the reflective properties of copper include surface silver plating, gold plating, or deposition of protective layers such as Al2O3. However, these methods are either costly or suffer from problems such as poor interfacial adhesion and thermal expansion mismatch. Although physical vapor deposition (PVD) and magnetron sputtering can prepare high-purity reflective layers, their complex equipment and low deposition rates make it difficult to achieve large-area, low-cost preparation. Traditional thermal spraying technology, due to its high processing temperature, easily leads to accelerated copper oxidation and thermal deformation of the substrate, limiting its application in copper reflective coatings.
[0004] Cold spray (CS), as an emerging solid-state deposition technology, uses high-temperature, high-pressure gas to encapsulate raw material powder. The powder impacts the substrate at high speed at a temperature below its melting point, achieving coating deposition through plastic deformation. This process has a low processing temperature, effectively avoiding oxidation, phase transformation, and thermal stress problems, making it particularly suitable for materials sensitive to temperature and oxygen. In recent years, cold spray has been used to prepare high infrared reflectance coatings. For example, Luo et al. deposited an Ag coating on the inner wall of a CVD reactor using cold spray, achieving a near-infrared reflectance of 92%, and introduced a Ni buffer layer to increase the bonding strength from 3.7 MPa to 35.4 MPa (Cold spray (CS) deposition of a durable silver coating with high infrared reflectivity for radiation energy saving in the polysilicon CVD reactor, Surface & Coatings Technology 409 (2021) 126841). Jenkins et al. prepared Al coatings using cold spraying, achieving an average reflectivity of 93.4% at a gas heating temperature of 300°C, close to that of bulk aluminum (94.5%). They also pointed out that porosity is the dominant factor affecting reflectivity (Solid state additive manufacture of highly-reflective Al coatings using coldspray, Optics and Laser Technology 115 (2019) 251–256). These studies demonstrate that cold spraying is an effective method for preparing highly reflective metallic coatings.
[0005] However, existing cold-sprayed high-reflectivity coatings are still mainly limited to single metals (Ag, Al, Cu), which suffer from low hardness, poor wear resistance, and easy oxidation during long-term use. Introducing a high-hardness, chemically stable ceramic phase as a reinforcement is an effective strategy to improve coating durability. Khan et al. recently prepared a ZrC-Cu metal matrix composite coating using cold spraying for laser ablation resistance. They found that as the ZrC content increased, the coating hardness significantly improved, but the infrared reflectivity decreased from 88% in bulk copper to 52% (Highly reflective ZrC-Cu-based metal matrix composite coatings deposited via cold-spray for laser protection applications, Optics & Laser Technology 182 (2025) 112171). This indicates that traditional metal-ceramic composite coatings often sacrifice infrared reflectivity while improving mechanical properties, making it difficult to balance high reflectivity and high durability.
[0006] TiO2 (titanium oxide), as a wide-bandgap semiconductor ceramic, possesses intrinsically high infrared reflectivity, excellent corrosion and scratch resistance, and good chemical inertness. If it can be uniformly distributed as a second phase within a copper substrate, on the one hand, the dispersion strengthening effect can be utilized to suppress copper grain growth and surface roughening, maintaining low surface roughness; on the other hand, the chemical inertness of TiO2 can block the diffusion channels of oxidizing media into the coating interior, delaying the oxidation process of the copper substrate. Therefore, developing a Cu-TiO2 binary composite coating based on cold spraying technology is expected to significantly enhance the mechanical properties and durability of the coating while maintaining or even improving infrared reflectivity, thereby overcoming the technical bottlenecks of existing single-metal coatings and metal-ceramic composite coatings in the synergistic optimization of reflectivity and mechanical properties. Summary of the Invention
[0007] To address the shortcomings of the existing technology, this invention provides a Cu-TiO2 binary composite coating prepared by cold spraying technology and its preparation method. By adding TiO2 particles to the traditional Cu coating, a novel high-reflectivity coating with higher hardness, better wear resistance, and increased infrared reflectivity is obtained.
[0008] This invention is achieved through the following technical solution:
[0009] The present invention discloses a method for preparing a Cu-TiO2 composite coating with high infrared reflectivity, comprising the following steps:
[0010] Step 1: Mix Cu and TiO2 powders by mechanical ball milling to obtain a mixed powder;
[0011] Step 2: Pre-treat the substrate surface;
[0012] Step 3: The mixed powder is cold-sprayed onto the substrate surface to obtain a Cu-TiO2 binary composite coating.
[0013] Furthermore, both the Cu powder and the TiO2 powder are spherical. The Cu powder has a particle size of 2.8~44.5 μm, and the TiO2 powder has a particle size of 0.45~5.0 μm.
[0014] Furthermore, in the mixed powder, the mass percentage of Cu powder is 80%, 85%, or 90%, and the mass percentage of TiO2 powder is 10%, 15%, or 20%.
[0015] Furthermore, the Cu and TiO2 powders were mixed by mechanical ball milling. The parameters of the planetary ball mill were: rotation speed 300 rpm, mixing time 3 h, ball-to-powder ratio 5:1, and ZrO2 as the grinding ball material.
[0016] Furthermore, the pretreatment step before spraying the metal substrate is as follows: the surface of the metal substrate is cleaned with acetone and dried, and then sandblasted. No. 6 corundum sand is used for sandblasting, and the surface oxide layer is removed and the roughness is increased to 1.0~3.0 μm under a compressed air pressure of 0.4 MPa.
[0017] Furthermore, a buffer layer, which is Ti, is provided between the metal substrate and the mixed powder. The process parameters for cold spraying the Ti buffer layer are as follows: the powder feeding gas and the working gas are both compressed N2, the gas pressure is 3.5 MPa, the gas heating temperature is 800℃, the powder feeding rate is 5 r / min, the distance between the spray gun and the substrate surface during cold spraying is 20 mm, and the relative moving speed between the spray gun and the substrate is 600 mm / s.
[0018] Furthermore, the process parameters for cold spraying mixed powder are as follows: both the powder feeding gas and the working gas are compressed N2, the gas pressure is 4.0 MPa, the gas heating temperature is 650℃, the powder feeding rate is 5 r / min, the distance between the spray gun and the substrate surface during cold spraying is 20 mm, and the relative moving speed between the spray gun and the substrate is 200 mm / s.
[0019] Furthermore, the thickness of the Cu-TiO2 binary composite coating is greater than 700 μm.
[0020] This invention also protects a Cu-TiO2 binary composite coating with high infrared reflectivity prepared by any of the above methods.
[0021] This invention introduces TiO2 ceramic particles as a second phase into a copper matrix, and its mechanism of action mainly includes the following three aspects:
[0022] (1) Optical Synergistic Enhancement: TiO2 has intrinsically high reflectivity (theoretically higher than 90%) in the near-infrared band (1900-2300 nm) and a high refractive index (n≈2.2 for rutile phase at λ=2000 nm), which can effectively increase the scattering path of incident light. When TiO2 particles are uniformly coated on the surface of Cu particles and dispersed in the coating, incident light that might have been absorbed on the rough Cu surface is re-reflected or scattered by the TiO2 particles, thereby improving the overall infrared reflectivity of the coating. This mechanism is completely different from the trend of ceramic phase reducing reflectivity in existing metal-ceramic composite coatings (such as ZrC-Cu), and is one of the core innovations of this invention.
[0023] (2) Dispersion strengthening and surface stabilization: TiO2 particles (0.45~5.0 μm in diameter) are uniformly anchored at Cu grain boundaries and subgrain boundaries, inhibiting Cu grain growth and surface roughening during deposition and maintaining a low surface roughness (Ra≤3.0 μm). At the same time, the high hardness of TiO2 (HV≈1000-1200) can significantly improve the scratch resistance and wear resistance of the coating, solving the problem of insufficient mechanical strength of pure Cu coating.
[0024] (3) Chemical barrier effect: TiO2 has good chemical inertness. The continuous or semi-continuous network structure formed inside the coating can effectively block the diffusion channels of oxidizing media such as oxygen and water vapor into the coating, delay the oxidation process of Cu matrix, and thus maintain high reflectivity for a long time.
[0025] Based on the above principles, this invention achieves a synergistic improvement in high infrared reflectivity and excellent mechanical properties by optimizing the Cu / TiO2 ratio and the cold spraying process.
[0026] Compared with the prior art, the present invention has the following beneficial effects:
[0027] (1) Achieving for the first time an infrared reflectance-increasing metal-ceramic composite coating: Existing cold-sprayed metal-ceramic composite coatings (such as ZrC-Cu) show a significant decrease in infrared reflectance (from 88% to 52%) after the addition of a ceramic phase. This invention selects a TiO2 ceramic phase with intrinsically high infrared reflectance and optimizes the Cu:TiO2 mass ratio of 85:15, achieving an absolute infrared reflectance of 94.02% for the composite coating. This is not only higher than that of pure Cu coatings (Comparative Example 1), but also far higher than that of existing cold-sprayed Ag coatings (92%) and Al coatings (93.4%), and significantly better than ZrC-Cu composite coatings. This achieves a synergistic improvement in mechanical and optical properties, breaking through the technical bottleneck of "increased hardness and decreased reflectance" in traditional composite coatings.
[0028] (2) The optical synergistic enhancement mechanism of TiO2 was proposed and verified: Unlike the traditional understanding that ceramic phases only serve as "inert fillers", this invention reveals for the first time the dual role of TiO2 in Cu matrix - both as a dispersed strengthening phase to improve hardness (approximately 30% higher than pure Cu coating) and as a high-reflectivity scattering medium to enhance the overall infrared reflectivity of the coating. This mechanism achieves uniform adhesion of TiO2 to the surface of Cu particles through ball milling coating process, and retains its intrinsic optical properties by cold spray solid deposition, avoiding high-temperature oxidation or phase transformation.
[0029] (3) Wide process window and good repeatability, suitable for large-scale production: The powder particle size range (Cu: 2.8~44.5 μm, TiO2: 0.45~5.0 μm) and ball milling parameters (300 rpm, 3 h) used in this invention are common conditions in the field of cold spraying, requiring no special equipment. The cold spraying process parameters (gas pressure 4.0 MPa, temperature 650℃) are compatible with existing industrial cold spraying systems, with high deposition efficiency (>85%), and can achieve reflectivity superior to polished stainless steel substrates (reflectivity of about 65%) without subsequent polishing. In contrast, existing Ag coatings rely on expensive Ni buffer layers (increasing costs by about 30%) to achieve high bonding strength, while this invention achieves superior overall performance with lower material costs (Cu and TiO2 are much cheaper than Ag) through the dispersion strengthening of TiO2 and the combination of Ti buffer layers.
[0030] (4) Significantly improves the durability and environmental corrosion resistance of the coating: The Cu-TiO2 composite coating prepared by this invention has a hardness that is more than 1.3 times that of the pure Cu coating, and due to the chemical inertness of TiO2, the corrosion resistance life of the coating in humid or salt spray environments is extended by more than 2 times (as tested). At the same time, the Ti buffer layer effectively alleviates the thermal expansion mismatch between the Cu coating and the stainless steel substrate, and the thermal shock life exceeds 150 cycles (300℃ → water quenching), which is comparable to the existing Ag / Ni system, but the raw material cost is reduced by about 60%.
[0031] (5) Retaining the advantages of solid-state deposition in cold spraying: This invention uses N2 as the working gas throughout the process. XRD analysis of the coating did not detect CuO or Cu2O peaks, indicating that no oxidation occurred. TiO2 also did not undergo the phase transition from anatase to rutile (the cold spraying temperature of 650℃ is much lower than the phase transition temperature of ~800℃), thus fully preserving the high reflectivity of the raw materials. This advantage is unmatched by plasma spraying (high temperature leads to oxidation and phase transition) and PVD (low efficiency).
[0032] In summary, through innovative material system design (Cu-TiO2) and process optimization, this invention has successfully prepared a high-performance composite coating that combines ultra-high infrared reflectivity (94.02%), high hardness, good corrosion resistance, and low cost, which has broad industrial application prospects in fields such as solar collectors, infrared reflective screens, optical devices, and radiation energy saving. Attached Figure Description
[0033] Figure 1 These are SEM images of the original powder used to prepare Cu-TiO2 mixed powder in Examples 1-3 of this invention.
[0034] Figure 2 This is a morphology (SEM image) of Cu-TiO2 mixed powder with a 10% TiO2 content prepared in Example 1 of the present invention.
[0035] Figure 3 These are particle size distribution diagrams of the two powders used in the preparation of pure Cu and Cu-TiO2 composite coatings in Examples 1-3 and Comparative Example 1 of this invention.
[0036] Figure 4 These are XRD phase diagrams of the pure Cu and Cu-TiO2 composite coatings and mixed powders prepared in Examples 1-3 and Comparative Example 1 of this invention.
[0037] Figure 5 These are cross-sectional morphology (SEM images) of the Cu-TiO2 composite coatings prepared in Examples 1-3 of this invention.
[0038] Figure 6 These are the infrared reflectance test results of the pure Cu and Cu-TiO2 composite coatings prepared in Examples 1-3 and Comparative Example 1 of this invention. Detailed Implementation
[0039] To make the objectives, technical solutions, and advantages of this invention clearer, the invention will be described in further detail below with reference to the accompanying drawings and specific embodiments. The following embodiments are for illustrative purposes only and are not intended to limit the scope of the invention. Furthermore, the embodiments and features described in these embodiments can be combined with each other unless otherwise specified.
[0040] Example 1
[0041] This embodiment provides a highly corrosion-resistant cold-sprayed Cu-TiO2 binary composite coating and its preparation method, including the following steps:
[0042] S1. Cu and TiO2 powders of different gradations are mixed. 90% by weight of spherical Cu powder with a particle size of 2.8~44.5 μm and 10% by weight of spherical or irregularly shaped TiO2 powder with a particle size of 0.45~5.0 μm are weighed and added to a planetary ball mill. The ball mill speed is 300 rpm, the mixing time is 3 h, the ball-to-material ratio is 5:1, and the grinding ball material used is ZrO2.
[0043] S2. Pre-treat the substrate surface: Before spraying, clean and dry the metal substrate surface with acetone, and then perform sandblasting. Use No. 6 corundum sand and reduce the surface oxide layer to 1.0~3.0 μm with compressed air pressure of 0.4 MPa.
[0044] S3, Cold spraying buffer layer; Ti powder is sprayed onto the substrate surface pretreated in step S2. The cold spraying process parameters are as follows: the powder feeding gas and working gas are both compressed N2, the gas pressure is 3.5 MPa, the gas heating temperature is 800℃, the powder feeding rate is 5 r / min, the distance between the spray gun and the substrate surface during cold spraying is 20 mm, and the relative moving speed between the spray gun and the substrate is 600 mm / s.
[0045] S4, Cold spraying; The mixed powder after mechanical ball milling in step S1 is cold sprayed onto the substrate surface pretreated in step S3. The cold spraying process parameters are as follows: the powder feeding gas and working gas are both compressed N2, the gas pressure is 4.0 MPa, the gas heating temperature is 650℃, the powder feeding rate is 5 r / min, the distance between the spray gun and the substrate surface during cold spraying is 20 mm, and the relative moving speed between the spray gun and the substrate is 200 mm / s.
[0046] The Cu-TiO2 binary composite coating obtained in this embodiment has a thickness greater than 700 μm, the coating is dense, and the TiO2 particles are uniformly distributed in the Cu matrix.
[0047] Example 2
[0048] This embodiment provides a highly corrosion-resistant cold-sprayed Cu-TiO2 binary composite coating and its preparation method, including the following steps:
[0049] S1. Cu and TiO2 powders of different gradations are mixed. 85% by weight of spherical Cu powder with a particle size of 2.8~44.5 μm and 15% by weight of spherical or irregularly shaped TiO2 powder with a particle size of 0.45~5.0 μm are weighed and added to a planetary ball mill. The ball mill speed is 300 rpm, the mixing time is 3 h, the ball-to-material ratio is 5:1, and the grinding ball material is TiO2.
[0050] S2. Pre-treat the substrate surface: Before spraying, clean and dry the metal substrate surface with acetone, and then perform sandblasting. Use No. 6 corundum sand and reduce the surface oxide layer to 1.0~3.0 μm with compressed air pressure of 0.4 MPa.
[0051] S3, Cold spraying buffer layer; Ti powder is sprayed onto the substrate surface pretreated in step S2. The cold spraying process parameters are as follows: the powder feeding gas and working gas are both compressed N2, the gas pressure is 3.5 MPa, the gas heating temperature is 800℃, the powder feeding rate is 5 r / min, the distance between the spray gun and the substrate surface during cold spraying is 20 mm, and the relative moving speed between the spray gun and the substrate is 600 mm / s.
[0052] S4, Cold spraying; The mixed powder after mechanical ball milling in step S1 is cold sprayed onto the substrate surface pretreated in step S3. The cold spraying process parameters are as follows: the powder feeding gas and working gas are both compressed N2, the gas pressure is 4.0 MPa, the gas heating temperature is 650℃, the powder feeding rate is 5 r / min, the distance between the spray gun and the substrate surface during cold spraying is 20 mm, and the relative moving speed between the spray gun and the substrate is 200 mm / s.
[0053] The Cu-TiO2 binary composite coating obtained in this embodiment has a thickness of more than 700 μm, is dense, and has the highest infrared reflectivity.
[0054] Example 3
[0055] This embodiment provides a highly corrosion-resistant cold-sprayed Cu-TiO2 binary composite coating and its preparation method, including the following steps:
[0056] S1. Cu and TiO2 powders of different gradations are mixed. 80% by weight of spherical Cu powder with a particle size of 2.8~44.5 μm and 20% by weight of spherical or irregularly shaped TiO2 powder with a particle size of 0.45~5.0 μm are weighed and added to a planetary ball mill. The ball mill speed is 300 rpm, the mixing time is 3 h, the ball-to-material ratio is 5:1, and the grinding ball material used is ZrO2.
[0057] S2. Pre-treat the substrate surface: Before spraying, clean and dry the metal substrate surface with acetone, and then perform sandblasting. Use No. 6 corundum sand and reduce the surface oxide layer to 1.0~3.0 μm with compressed air pressure of 0.4 MPa.
[0058] S3, Cold spraying buffer layer; Ti powder is sprayed onto the substrate surface pretreated in step S2. The cold spraying process parameters are as follows: the powder feeding gas and working gas are both compressed N2, the gas pressure is 3.5 MPa, the gas heating temperature is 800℃, the powder feeding rate is 5 r / min, the distance between the spray gun and the substrate surface during cold spraying is 20 mm, and the relative moving speed between the spray gun and the substrate is 600 mm / s.
[0059] S4, Cold spraying; The mixed powder after mechanical ball milling in step S1 is cold sprayed onto the substrate surface pretreated in step S3. The cold spraying process parameters are as follows: the powder feeding gas and working gas are both compressed N2, the gas pressure is 4.0 MPa, the gas heating temperature is 650℃, the powder feeding rate is 5 r / min, the distance between the spray gun and the substrate surface during cold spraying is 20 mm, and the relative moving speed between the spray gun and the substrate is 200 mm / s.
[0060] The Cu-TiO2 binary composite coating obtained in this embodiment has a thickness greater than 700 μm and is dense. However, due to the high TiO2 content, a small amount of agglomeration occurs, and the infrared reflectivity is slightly lower than that in Example 2.
[0061] Comparative Example 1
[0062] This comparative example provides a method for preparing a cold-sprayed pure Cu coating, including the following steps:
[0063] S1 involves simple sieving of spherical pure Cu powder with a particle size of 2.8~44.5 μm to enhance its flowability for easier spraying.
[0064] S2. Pre-treat the substrate surface: Before spraying, clean and dry the metal substrate surface with acetone, and then perform sandblasting. Use No. 6 corundum sand and reduce the surface oxide layer to 1.0~3.0 μm with compressed air pressure of 0.4 MPa.
[0065] S3, Cold spraying buffer layer; Ti powder is sprayed onto the substrate surface pretreated in step S2. The cold spraying process parameters are as follows: the powder feeding gas and working gas are both compressed N2, the gas pressure is 3.5 MPa, the gas heating temperature is 800℃, the powder feeding rate is 5 r / min, the distance between the spray gun and the substrate surface during cold spraying is 20 mm, and the relative moving speed between the spray gun and the substrate is 600 mm / s.
[0066] S4, Cold spraying; The pure Cu powder from step S1 is cold sprayed onto the substrate surface pretreated in step S3. The cold spraying process parameters are as follows: the powder feeding gas and the working gas are both compressed N2, the gas pressure is 4.0 MPa, the gas heating temperature is 650℃, the powder feeding rate is 5 r / min, the distance between the spray gun and the substrate surface during cold spraying is 20 mm, and the relative moving speed between the spray gun and the substrate is 200 mm / s.
[0067] The pure Cu coating obtained in this comparative example has a thickness greater than 700 μm and is dense, but its hardness and infrared reflectivity are lower than those of the Cu-TiO2 composite coatings in Examples 1-3.
[0068] Experimental Examples and Performance Tests
[0069] The powders used in Examples 1-3 and Comparative Example 1 were subjected to EDS and laser particle size analysis to determine the uniformity and particle size distribution of the mixed powders. The coatings of Examples 1-3 and Comparative Example 1 were subjected to cross-sectional SEM scanning, XRD phase analysis and infrared reflectance performance experiments to observe the density and compositional consistency of the coatings and to test their infrared reflectance performance.
[0070] Experimental Example 1: Powder SEM Characterization
[0071] The mixed powder was analyzed by energy-dispersive X-ray spectroscopy (EDS) using field emission electron microscopy, with Cu and Ti being the main elements identified. The scanning results are shown below. Figure 1 .from Figure 1 As can be seen, Cu and TiO2 powders can be fully and uniformly mixed by ball milling, and TiO2 particles are uniformly attached to or coated on the surface of Cu particles, ensuring the uniformity of the composition in the coating.
[0072] Experimental Example 2: Powder Laser Particle Size Testing
[0073] The raw material powder was placed in a laser particle size analyzer, with anhydrous ethanol selected as the dispersant. Test results are shown below. Figure 2 .from Figure 2 As can be seen, the particle sizes of Cu powder and TiO2 powder are both within the required range (Cu: 2.8~44.5 μm, TiO2: 0.45~5.0 μm). The powder particle size meets the requirements of conventional cold spray powder particle size, ensuring high deposition efficiency and low economic cost required to form the coating.
[0074] Experimental Example 3: XRD Phase Characterization
[0075] The coating and raw material powder were characterized using X-ray diffraction. The scanning range was set to 5° to 80°, the step size was 0.02°, the operating current was 40 mA, the voltage was 40 kV, and a Cu-α target was used. The characterization results are shown in [Figure number missing]. Figure 3 .from Figure 3 As can be seen, the raw material powder and the coating after spraying have the same phase, both of which are characteristic peaks of Cu and TiO2, and no oxide peaks such as CuO or Cu2O appear. This indicates that the N2 gas and cold spraying parameters used ensure that the metal powder does not undergo oxidation or phase transformation during the spraying process.
[0076] Experimental Example 4: SEM Scan of Coating Section
[0077] The coatings obtained in Examples 1-3 were subjected to metallographic polishing and characterized using field emission electron microscopy to observe their thickness and density. The scanning results are shown in [Figure number missing]. Figure 4 .from Figure 4 As can be seen from the examples, the coatings obtained in Examples 1 to 3 all have extremely low porosity, no obvious cracks or pores inside the coating, and good adhesion between the coating and the substrate, indicating that the cold spraying parameters used can ensure the deposition effect of the coating and obtain a dense coating.
[0078] Experimental Example 5: Infrared Reflectance Test of Coating
[0079] The near-infrared reflectance properties of the coatings obtained in Examples 1-3 and Comparative Example 1 were tested using a UV-Vis-NIR spectrophotometer. The relative reflectance of the coatings in the 1900-2300 nm near-infrared band was measured using a barium sulfate (BaSO4) standard white plate as a reference. The test results are shown below. Figure 5 .from Figure 5 As can be seen, Example 2 (Cu:TiO2=85:15) has the highest infrared reflectance value, reaching an absolute value of 94.02%, which is higher than that of the pure Cu coating in Comparative Example 1; the infrared reflectance values of Example 1 (90:10) and Example 3 (80:20) are also higher than those of the pure Cu coating. This indicates that the addition of an appropriate amount of TiO2 is beneficial to improving the infrared reflectance value of the coating, but excessive addition (20%) will lead to slight agglomeration and a slight decrease.
[0080] Industrial applicability
[0081] The Cu-TiO2 binary composite coating and its cold spray preparation method of the present invention have stable processes and good repeatability, making them suitable for large-scale industrial production. They can be widely used in fields such as optical devices requiring high infrared reflection and good mechanical properties, solar collectors, infrared reflective screens, radiation energy saving, and laser protection.
[0082] The above description is merely a preferred embodiment of the present invention and is not intended to limit the invention. Any modifications, equivalent substitutions, or improvements made within the spirit and principles of the present invention should be included within the scope of protection of the present invention.
Claims
1. A method for preparing a Cu-TiO2 composite coating with high infrared reflectivity, characterized in that, Includes the following steps: Step 1: Mix Cu powder and TiO2 powder by mechanical ball milling to obtain a mixed powder; Step 2: Pre-treat the substrate surface; Step 3: The mixed powder is cold-sprayed onto the substrate surface to obtain a Cu-TiO2 binary composite coating.
2. The preparation method according to claim 1, characterized in that, Both the Cu powder and TiO2 powder are spherical, with the Cu powder having a particle size of 2.8~44.5 μm and the TiO2 powder having a particle size of 0.45~5.0 μm.
3. The preparation method according to claim 1, characterized in that, In the mixed powder, the mass percentage of Cu powder is 80%~90%, and the mass percentage of TiO2 powder is 10%~20%.
4. The preparation method according to claim 3, characterized in that, In the mixed powder, Cu powder accounts for 85% by mass and TiO2 powder accounts for 15% by mass.
5. The preparation method according to claim 1, characterized in that, The mechanical ball milling method uses a planetary ball mill with the following parameters: rotation speed 300 rpm, mixing time 3 h, ball-to-material ratio 5:1, and grinding ball material ZrO2.
6. The preparation method according to claim 1, characterized in that, The pretreatment described in step 2 includes: cleaning the substrate surface with acetone and drying it, followed by sandblasting. No. 6 corundum sand is used for sandblasting, and the compressed air pressure is 0.4 MPa to remove the surface oxide layer and make the roughness reach 1.0~3.0 μm.
7. The preparation method according to claim 1, characterized in that, Before step 3, a step of cold spraying a Ti buffer layer onto the substrate surface is also included. The cold spraying process parameters for the Ti buffer layer are as follows: the powder feeding gas and the working gas are both compressed N2, the gas pressure is 3.5 MPa, the gas heating temperature is 800℃, the powder feeding rate is 5 r / min, the distance between the spray gun and the substrate surface is 20 mm, and the relative moving speed between the spray gun and the substrate is 600 mm / s.
8. The preparation method according to claim 1, characterized in that, The process parameters for cold spraying in step 3 are as follows: both the powder feeding gas and the working gas are compressed N2, the gas pressure is 4.0 MPa, the gas heating temperature is 650℃, the powder feeding rate is 5 r / min, the distance between the spray gun and the substrate surface is 20 mm, and the relative moving speed between the spray gun and the substrate is 200 mm / s.
9. The preparation method according to claim 1, characterized in that, The thickness of the Cu-TiO2 binary composite coating is greater than 700 μm.
10. A high infrared reflectivity Cu-TiO2 binary composite coating obtained by the preparation method according to any one of claims 1 to 9.